Market entry strategy of Ben & Jerry’s to the Russian market : is there market for a sustainable brand in the Russian Federation? - Gasanov, Gasan (2021)
The following Master’s thesis is devoted to the analysis of Ben & Jerry’s entry strategy with a focus on CSR activities. The main goals of the Master’s thesis are to develop a comprehensive market entry strategy of Ben & Jerry’s to the Russian market and evaluate consumers’ attitude towards CSR activities in Russia. To accomplish the goals of the thesis, secondary data from the most relevant studies and statistical databases were used, and qualitative research for a better understanding of the perception of CSR was conducted. The theoretical part of the thesis is devoted to the main concepts of a marketing plan, which are necessary for the successful implementation of a market entry strategy. The practical part includes the implementation of the market entry strategy of Ben & Jerry itself. It focuses on the macro and microenvironment of the Russian market. As a result of the research, it was revealed that Ben & Jerry’s can successfully integrate into the Russian market.